VALIDITAS MULTIMEDIA PEMBELAJARAN INTERAKTIF PADA MATERI SISTEM KOORDINASI MANUSIA KELAS XI SMA - Athaya Hasna Abiyya; Wan Syafi’i; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Interactive learning multimedia is a learning media that contains a combination of text, images, video, sound, animation and simulation synergistically with the help of technological devices to achieve learning goals, where users can actively interact with the media. This study aims to produce interactive learning multimedia on valid high school class XI human coordination system material. The research was carried out at the Biology Education Campus, FKIP, Riau University and SMAN 8 Pekanbaru. The type of research used is ADDIE which consists of the Analysis, Design and Development stages. The data collection instrument used was a validation sheet. The validation results based on aspects of material structure, learning design, language, audio-visual display and practical and efficient are 3.90, 3.89, 3.78, 3.77 and 3.65 respectively. The aspect that obtained the highest validation results was the material structure aspect with an average of 3.90 in a very valid category. Overall, interactive learning multimedia on human coordination system material for class XI SMA obtained a validation result of 3.80 and was included in the very valid category. Thus the interactive learning multimedia that has been developed is suitable for use as a learning medium in the human coordination system material for class XI SMA.Key Words: Interactive Learning Multimedia, Human Coordination System